Integration of vanadium redox battery (VRB) in DC microgrid - Ng, Wei Jie (2017)
Vanadium Redox Battery (VRB) has recently appeared to be a promising energy storage technology for grid-scale application. In term of providing ancillary services to an electrical network, studies showed that VRB possesses many advantages over conventional battery storage systems which are commonly adopted, such as longer lifetime cycle, inherently safe and non-flammable, higher cost efficiency and etc. Past researches mainly focused on the optimal sizing of VRB for cost reduction and its implementation issues in AC grid application. However, DC distributed generation is getting more important as well with the increasing penetration of renewable energy. This paper presents the practical analysis of the VRB integration in a DC microgrid. The first part of the paper illustrates the design of a DC/DC boost converter and PI controller for the integration purpose. The key working principle is discussed and the model parameters for the components are calculated based on theoretical analysis. Numerous tests are carried out to justify the results and performances. The second part of the paper focuses on the MATLAB simulation and experimental result analysis. The functionality of the integrated system is justified through experiments and satisfactory results are obtained in overall. To increase the viability and practicality, ultracapacitor is added as a second source apart from VRB to realize a hybrid system. Traditional droop control methodology is applied. The integration and implementation issues met in this study are also addressed and briefly discussed.